Organizational Cultural Traits: the Relationship between Transformational Leadership Style and Corporate Members' Attitudes - Arman Hadi, Abdul Manaf; Juhary, Ali (2012)
This study investigates the relationships between transformational leadership styles, organizational culture, and members’ attitudinal outcomes on their level of job satisfaction, organizational commitment, and trust in management. This study was conducted on corporate members at the managerial levels, with a total of 364 responses (n = 364) from the selected government-linked companies (GLCs) which are currently in the GLC Transformation Program controlled by GLIC (government-linked investments companies) such as Khazanah Nasional, an investment holding arm of the government of Malaysia and also constituents of Putrajaya Committee GLC High Performance (PCG). The samples of respondents were also extended to the GLCs listed in the main board of the Kuala Lumpur Stock Exchange (KLSE). Hierarchical multiple regression analysis was used to investigate the relationships. Hierarchical multiple regression analysis was used to investigate the relationships. The results of this study showed that cultural traits were positively demonstrated as a mediator in linking the relationship between transformational leadership styles and corporate members’ attitudinal outcomes. The traits of culture practiced in an organization through leadership are the main elements to designing and strategizing the way an organization works in order to deliver tangible and sustainable results in the future. This study contributes to the dynamics of the causative relations between leadership styles, cultural traits and managerial attitudes in the organization .